PELATIHAN PEMBUATAN FOOTSANITIZER DARI BIJI KOPI dan JAHE PADA SISWA DI SMK AL AMIN DUKUHTURI - Febriyanti, Rizki; Muldiyana, Tya; Sugiharto, Siswoyo (LPPM Universitas Flores, 2024)
Health problems are one of the important things that all sectors must consider, starting from the family, teachers, staff, and students. The feet are one part of the body that often sweat. Moreover, if the feet are almost always covered with shoes throughout the day in hot weather, it will cause an unpleasant odor to stick to the feet. Foot odor is caused by a buildup of bacteria that breeds on damp feet. So the solution offered is training in making foot sanitizers using natural ingredients, namely ginger and coffee extracts. This community service activity aims to improve health knowledge and skills for Al Amin Vocational High School students. In addition, it is also expected to be beneficial for various parties, especially for participants, teachers, staff and the surrounding community. From the PKM activities that have been carried out, it can be concluded that increasing knowledge, understanding and training regarding foot sanitizer products with coffee bean extract and ginger with several concepts provided include: counselling about foot odor, the benefits of using foot sanitizers, processing the manufacture of foot sanitizer from coffee bean extract for students and students of SMK Al Amin Dukuhturi according to the level of knowledge that they easily understand. Where is the foot sanitizer preparation from a combination of coffee and ginger as a way out to maintain foot health and hygiene that is practical and easy to carry.